MECHANICAL INVESTIGATION OF HEAT-TREATED ADDITIVELY MANUFACTURED Ti-6Al-4V-Ta ALLOY FOR STRUCTURAL APPLICATIONS - Omenov, Yerseit (Nazarbayev University School of Engineering and Digital Sciences, 2025)
Titanium alloys are one of the significant materials utilized in many engineering industries. Additive manufacturing is a recent technology that enables the production of metal components, including titanium, alternatively to traditional methods. Various modifications and procedures can be utilized to improve the physical properties of material for different purposes. Elemental alloying is one of the most effective techniques aimed at altering microstructure. The thesis investigates mechanical characterization of 3D-printed titanium alloy, Ti-6Al-4V, mixed with 8% tantalum (Ta). Crucial properties of manufactured parts designed for structural applications are ductility and fatigue performance. Heat treatment procedures are typical post-processing steps that reduce internal stress, thus improving ductility. Two types of specimens, as-built and heat-treated, were prepared for mechanical tests to observe the influence of implemented heating methodology. Both static and dynamic tests were conducted, along with microstructural analysis, phase transformation study, and electrochemical corrosion experiments, to understand performance changes. Despite the popularity of Ti-6Al-4V in additive manufacturing studies, extensive research on various heat treatment procedures, and tantalum addition separately, there is limited information available on the fatigue performance of heat-treated, elementally alloyed Ti-6Al-4V with Ta. The methodology includes extensive mechanical characterization of heat-treated Ti-6Al-4V 8%Ta alloy material. Tensile, compression, microhardness, and fatigue tests were performed to compare the material properties, and microstructural analysis was conducted to understand the material’s response to applied stress. Moreover, the electrochemical corrosion experiment imitated the real-world corrosive environment to assess developed specimens. The thesis is aimed at investigating mechanically mixed, SLM-printed Ti-6Al-4V-8%Ta specimens, focusing on the resulting microstructural changes after heat treatment. It helps to understand the correlation between implemented methods and produced mechanical results. The obtained results are useful for assessing the suitability of SLM-printed components for structural applications.
Keywords: type of access: embargo